A Pilot Study to Assess Stool Sample Collection Methods for Gut Microbiome Research in Large Prospective Cohort Studies (FS07-01-19). (13th June 2019) - Um, Caroline; Lichtman, Cari; Stevens, Victoria; Gapstur, Susan; Patel, Alpa; McCullough, Marjorie
Abstract: Objectives: Colonic microbiota can be modified by diet and other environmental exposures that are associated with risk of cancer and other diseases. In addition, the stool metabolome represents products formed by gut microbial utilization of foods, nutrients, and other compounds. The collection of stool samples for analyses of the microbiome and metabolome in prospective cohort studies may lead to a better understanding of diet and other factors in disease etiology. Most studies of the gut microbiome and metabolome have been small clinical studies and relied on the collection of stool samples that were quickly flash-frozen and stored with no preservative. However, this method of collection is not feasible in large epidemiologic studies in which participants would self-collect and ship samples to a central repository. Other methods may preclude metabolomic analyses or result in a limited amount of stool. Methods: We designed a pilot study to inform stool collection procedures for participants enrolled in a nationwide prospective cohort study. In this pilot study, stool samples will be collected by 10 volunteers who will aliquot their sample into: 1) OMNIgene Gut collection kit, 2) 95% ethanol collection kit, (3) Fecal Occult Blood Test cards, and (4) a vial for fresh-frozen sample with no solution (i.e., the gold standard in this analysis). Fresh-frozen samples will be shipped overnight on dry ice to a central biorepository. The remaining samples will be: 1) shipped overnight on cold packs; 2) shipped overnight at ambient temperature; 3) shipped overnight after 4 days at ambient temperature; and 4) shipped overnight at ambient temperature, followed by 4-day incubation at 50 °C to mimic maximum shipment temperature. The reproducibility, stability, and accuracy of 16S sequencing and metabolomics in stool will be compared among the collection kits, and shipping and storage conditions. Results: Initial results are anticipated by June 2019. Conclusions: The findings of this pilot study will inform future stool collection among Cancer Prevention Study-3 (CPS-3) participants, which, when analyzed with food frequency questionnaire data, will broaden our understanding of the role of diet in cancer risk. Funding Sources: The American Cancer Society funds the creation, maintenance, and updating of CPS-3.